THE STUDENTS’ ABILITY IN COMPREHENDING PASSAGE THROUGH DISCUSSION WAY AT THE SECOND YEAR STUDENTS OF SMAN 1 KAUMAN TULUNGAGUNG IN THE EVEN SEMESTER ACADEMIC YEAR 2018/2019 - Gandjarwati, Yogo (Universitas Nusantara PGRI Kediri, 2019)
This study is a Classroom Action Research (CAR) about comprehending the passage through discussion way to improve the students’ reading skill. The population is 36 students at the second year of SMAN 1 Kauman. Instruments of the study consisted of reading test, observation check list and questionnaires. Based on the pre-test, the students’ reading skill and students’ motivation were still low, it was indicated that the score result was under minimum standard or the average score (70.14). Therefore, the researcher tried to apply the way of discussion in comprehending the passage to improve the reading skill. The writer found that in Cycle I the students’ score average was 74.44. The next cycle (Cycle II) done by the writer to improve the strategy in teaching reading through discussion way. It was proved that the students’ score average after the implementation of discussion was 80.12 . They passed and got the better score than previous result and the students’ motivation was also good. It could be seen from the result of observation data which showed that 91.6% students were more active in teaching learning process through discussion way. Then the students’ interest in reading comprehension through discussion way was also good. It is shown on the result of questionnaire in which there were 86.11% students interested in reading comprehension through discussion. It is concluded that the way of discussion in comprehending the passage was able to improve the students’ reading skill Keywords: comprehending, passage, discussion way Keywords: Comprehending, passage, discussion way